Does Lumbar Interbody Cage Size Influence Subsidence? A Biomechanical Study. Issue 2 (15th January 2020) - Yuan, Wei; Kaliya-Perumal, Arun-Kumar; Chou, Siaw Meng; Oh, Jacob Yoong-Leong
Abstract : Study Design: An experimental laboratory-based biomechanical study. Objective: To investigate the correlation between cage size and subsidence and to quantify the resistance to subsidence that a larger cage can provide. Summary of Background Data: The assumption that a bigger interbody cage confers less subsidence has not been proven. There was no previous study that has shown the superiority of lateral cages to bullet cages in terms of subsidence and none that has quantified the correlation between cage size and subsidence. Methods: A cage was compressed between two standardized polyurethane foam blocks at a constant speed. Four sizes of bullet cages used for transforaminal lumbar interbody fusion (TLIF) and six sizes of lateral cages used for lateral lumbar interbody fusion (LLIF) were tested. The force required for a 5 mm subsidence, axial area of cages, and stiffness were analyzed. Results: A larger cage required a significantly higher force for a 5 mm subsidence. Longer bullet cages required marginal force increments of only 6.2% to 14.6% compared to the smallest bullet cage. Lateral cages, however, required substantially higher increments of force, ranging from 136.4% to 235.7%. The average force of lateral cages was three times that of bullet cages (6426.5 vs. 2115.9 N), and the average stiffness of the LLIF constructs was 3.6 times that of the TLIF constructs (635.5 vs. 2284.2 N/mm). There was a strong correlation between the axial area of cages and the force for a 5 mm subsidence. Every 1 mm 2 increment of axial area corresponded to approximately 8 N increment of force. Conclusion: Cage size correlated strongly with the force required for a 5 mm subsidence. The LLIF constructs required higher force and were stiffer than the TLIF constructs. Among bullet cages, longer cages only required marginal increments of force. Lateral cages, however, required substantially higher force. Level of Evidence: N/A Abstract : In this biomechanical study, a simulated functional spinal unit was compressed to simulate subsidence. By analyzing the force, subsidence, and axial area of cage, we found that lumbar interbody fusion cage size correlated strongly with subsidence, and lateral cages were better in resisting subsidence than bullet cages.